PENGARUH KONSENTRASI MADU TERHADAP SIFAT FISIKOKIMIA DAN SIFAT ORGANOLEPTIK MINUMAN BELUNTAS-TEH HITAM DENGAN PERBANDINGAN 25:75% (B/B) - Anggraeni, Octavia Carolina; Widyawati, Paini Sri; Budianta, Dwi Wibawa (Widya Mandala Surabaya Catholic University, 2016)
Based on previous research is found the proportion of beluntas leaves powder and black tea the best of 25 : 75% (w/w). However, specially the discovery of the organoleptic properties (aroma and taste) that are less in demand by consumers and a decrease of total phenols, flavonoids, ability to scavenge free radicals, as well as the ability to reduce ferric (Fe3+) ion to ferrous (Fe2+) ion. One solution being taken to overcome these obstacles is the addition of honey as a sweetener and natural antioxidants. Research was conducted to determine the effect of honey concentration on physicochemical properties and organoleptic properties of functional beverage beluntas and black tea proportion of 25:75% (w/w). The research design was randomized block design with single factor. Factor that had been done the concentration of the honey including P1, P2, P3, P4, P5, and P6 (w/v). Each treatment had been repeated four times. The results showed that concentration of honey significantly affected on physicochemical properties and organoleptic properties of beverage product. Turbidity value was ranged from 6.31-20.14 NTU; pH value was ranged from 6.65-6.96; titratable acid was ranged from 0.0040-0.0177 mg gluconat acid/100 mL infusion; hue angle value was ranged from 25.49º-54.76º; and chroma value was ranged from 2.19-2.63. Appropiate concentration of honey to get the best treatment from organoleptic test was P6 with color value 7.14; flavour value 6.59; taste value 7.35; turbidity value 18.04 NTU; pH value 6.65; titratable acid value 0.0177 mg GAE/100 mL; hue angle value 25.49º; and chroma value 2.63.